c.1 - Wolfe, Christopher (New York, 1986)
This major history of judicial review, revised to include the Rehnquist court, shows how modern courts have used their power to create new "rights with fateful political consequences." Originally published by Basic Books.
Keywords: Judicial review- United States- History